The learning styles and the level development of the productive skills of the students of first, second and third years of bachillerato at Daniel Alvarez Burneo fiscomisional bachillerato high school of Loja city, academic year 2013-2014 - Jungal Arrobo, Monica Mirella (2015)
This research work entitled, THE LEARNING STYLES AND THE LEVEL DEVELOPMENT OF THE PRODUCTIVE SKILLS OF THE STUDENTS OF FIRST, SECOND AND THIRD YEARS OF BACHILLERATO AT ―DANIEL ÁLVAREZ BURNEO‖ FISCOMISIONAL BACHILLERATO HIGH SCHOOL OF LOJA CITY, ACADEMIC YEAR 2013-2014 was developed with the purpose of verify the influence of the learning styles in the level development of the productive skills of English language. The scientific, descriptive, analytical-synthetic and explicative methods, were implemented to develop this research. The surveys were applied to 307 students and 9 teachers, they were applied as instruments to collect the required data. Then they were tabulated, organized and described in the statistical tables, represented graphically, interpreted and analyzed in a logical process that allowed to formulate conclusions and recommendations. The results showed that teachers develop limitedly strategies based on the learning styles, and they do not help their students to develop the productive skills of the English language.